Selling over-the-counter medicines in food retail: Risk or opportunity? (Research, Society and Development, 2025)
Since 1973, the Brazilian Chamber of Deputies has been discussing the commercialisation of medicines in food retail. Bill 1.324 of 1995 proposed the commercialisation of at least the class of non-prescription medicines, but was rejected in 2004. Currently, the issue is still being discussed, through Bill 1,774 of 2019, with the justification of facilitating the population's access to medicines and thus reducing public health costs. The Federal and Regional Pharmacy Councils have always publicly expressed their opposition to all the bills presented, stating that no corporate interest can be greater than the rational use of medicines. The aim of this study was to carry out an integrative review of the literature on the risks and opportunities in favour of public health of marketing medicines in the food retail chain. The discussion divides opinion and must therefore be very well-founded so as not to put the population at risk, since the irrational use of medicines, often influenced by the media and without pharmaceutical assistance, can cause irreversible damage to the consumer's health and even generate additional costs for the Brazilian health system.